2012
DOI: 10.12968/ijpn.2012.18.4.197
|View full text |Cite
|
Sign up to set email alerts
|

A training needs analysis of neonatal and paediatric health-care staff in a tertiary children's hospital

Abstract: Understanding the educational needs of staff can underpin the development of appropriate educational interventions. These modules require evaluation to determine their impact on health professionals' knowledge and confidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 9 publications
1
15
0
3
Order By: Relevance
“…ACT (2009) updated by The Together for Short Lives (2017) neonatal pathway is one way of ensuring such an awareness, but this study highlighted the perception that the pathway was not used regularly in neonatal units. Such findings resonate with a previous study by Gallagher et al (2012) which showed that a high number of respondents to their survey felt they had not received enough education in children's palliative care, and few participants were aware of the ACT pathway. Therefore, this study supports the notion that healthcare professionals perceive a general lack of educational preparation for caring for infants and children who need palliative care.…”
Section: Discussionsupporting
confidence: 86%
“…ACT (2009) updated by The Together for Short Lives (2017) neonatal pathway is one way of ensuring such an awareness, but this study highlighted the perception that the pathway was not used regularly in neonatal units. Such findings resonate with a previous study by Gallagher et al (2012) which showed that a high number of respondents to their survey felt they had not received enough education in children's palliative care, and few participants were aware of the ACT pathway. Therefore, this study supports the notion that healthcare professionals perceive a general lack of educational preparation for caring for infants and children who need palliative care.…”
Section: Discussionsupporting
confidence: 86%
“…2 To develop appropriate educational content for Taiwanese clinicians, the educational needs of both neonatologists and neonatal nurses must be first identified. 2,11 Research Purposes…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, existing guidelines like those on European nursing education in palliative care devised by the European Association for Palliative Care (EAPC) task force [33] or the educational framework for pediatric palliative care developed in Ireland [34] can provide a basis for education tailored to particular regional needs [35] . Thereby, a good understanding of the educational desires of staff is essential to develop appropriate educational interventions [36] .…”
Section: Initial Situation Of Pediatric Palliative Home Care In Lowermentioning
confidence: 99%